2010
DOI: 10.1007/s12272-010-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

Spirafolide from bay leaf (Laurus nobilis) prevents dopamine-induced apoptosis by decreasing reactive oxygen species production in human neuroblastoma SH-SY5Y cells

Abstract: Reactive oxygen species (ROS) are important mediators in many neurodegenerative diseases including Alzheimer's disease and Parkinson's disease. This study tested the neuroprotective effects of spirafolide, a compound purified from the leaves of Laurus nobilis L. (Lauraceae), against dopamine (DA)-induced apoptosis in human neuroblastoma SH-SY5Y cells. Following a 24-h exposure of cells to DA (final conc., 0.6 mM), we observed a marked increase in apoptosis, increased generation of ROS and decreased cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Turkez et al [66] demonstrated the preventive role of L. nobilis leaf extract in alleviating aluminum phosphide-induced DNA and oxidative damages in vitro. Ham et al [67] reported that spirafolide from the bay leaf (L. nobilis) prevented dopamine-induced…”
Section: Effects Of Bay Leaf Incense (Bl) On the Hippocampus Oxidativmentioning
confidence: 99%
See 1 more Smart Citation
“…Turkez et al [66] demonstrated the preventive role of L. nobilis leaf extract in alleviating aluminum phosphide-induced DNA and oxidative damages in vitro. Ham et al [67] reported that spirafolide from the bay leaf (L. nobilis) prevented dopamine-induced…”
Section: Effects Of Bay Leaf Incense (Bl) On the Hippocampus Oxidativmentioning
confidence: 99%
“…Turkez et al [66] demonstrated the preventive role of L. nobilis leaf extract in alleviating aluminum phosphide-induced DNA and oxidative damages in vitro. Ham et al [67] reported that spirafolide from the bay leaf (L. nobilis) prevented dopamine-induced apoptosis by decreasing reactive oxygen species production in human neuroblastoma SH-SY5Y cells. BL exposure effectively restored the antioxidant defense mechanism by increasing the antioxidant levels of activity in the brain.…”
Section: Effects Of Bay Leaf Incense (Bl) On the Hippocampus Oxidativmentioning
confidence: 99%
“…Spirafolide is a compound purified from the leaves of Laurus nobilis L. It has been reported to decrease the ROS level, thereby inhibited dopamine-induced apoptosis in human neuroblastoma SH-SY5Y cells. 39 Fructose, when used as sole carbon source instead of glucose, reduced ROS and stabilized of cellular GSH pool as efficient as N-acetyl-cystein in the oxidative stress-induced apoptosis in liver parenchymal cells. 40 …”
Section: Natural/synthetic Antioxidants That Downregulate Reactive Oxmentioning
confidence: 99%
“…Recent reports were also exhibited the neuroprotective, cardioprotective and antidiabetic properties of LNE due to its antioxidant content. [2627] Dall’Acqua et al . [28] determined the phytochemical composition L. nobilis leaves and found ten different flavonoid O-glycosides, one flavonoid C-glycoside, catechin, and cinnamtannin B1.…”
Section: Discussionmentioning
confidence: 99%